Interfacial and thermophysical engineering for enhanced thermal performance of boron carbide-modified HITEC nanocomposites in high-temperature thermal energy storage applications - Gurgenc, Ezgi; Yamac, Halil Ibrahim; Ozabaci, Murat; Canbay, Canan Aksu; Gurgenc, Turan; Gur, Muhammed; Shahanaghi, Elshan Sefidgar (Elsevier, 2026)
HITEC-type nitrate-nitrite molten salts are promising heat transfer fluid and thermal energy storage media for intermediate-temperature concentrated solar power (CSP), yet their deployment is constrained by moderate heat-transfer capability and limited high-temperature robustness. This study introduces B4C as a non-oxide ceramic nanoadditive and systematically evaluates its structure-property impact in HITEC. Pristine HITEC and B4C-modified compositions (0.5 - 2.0 wt%) were synthesized using a unified protocol to enable direct comparison. Phase integrity and chemical framework preservation were examined by XRD and FT-IR, while morphology and additive distribution were assessed by FE-SEM/EDX. Thermophysical behavior was quantified by DSC for melting-solidification characteristics and temperature-dependent Cp, high-temperature stability was evaluated by TGA, and thermal conductivity was measured using the transient plane source method. The results show that B4C incorporation preserves the characteristic HITEC phase constitution and nitrate-nitrite bonding features, indicating predominantly physical integration. Thermal conductivity increases monotonically with loading and reaches a maximum enhancement of 50.42% at 2.0 wt% B4C. The liquid-phase Cp exhibits an optimum response, achieving a maximum enhancement of 34.25% at 1.5 wt% B4C. Phase-change energetics are strengthened, with the maximum melting enthalpy increase corresponding to 15.13% at 1.5 wt% B4C. Thermal stability is improved, as the decomposition onset shifts from 612 degrees C for pristine HITEC to 661 degrees C at 2.0 wt% B4C, corresponding to an 8.01% increase in upper operating temperature. Overall, these multi-parameter gains support HITEC-B4C nanocomposites as practical candidates for CSP-relevant operation requiring faster heat exchange, higher sensible storage density, and improved safety margins under cyclic service.
Keywords: Molten salt; HITEC; Boron carbide; Nanocomposite; Thermal energy storage; Thermal conductivity